Graphene-Based Aqueous Lubricants: Dispersion Stability to the Enhancement of Tribological Properties - Chouhan A.; Kumari S.; Sarkar T.K.; Rawat S.S.; Khatri O.P. (My University, 2025)
The present investigation demonstrates a green and scalable chemical approach to prepare aminoborate-functionalized reduced graphene oxide (rGO-AmB) for aqueous lubricants. The chemical, structural, crystalline, and morphological features of rGO-AmB are probed by XPS, FTIR, Raman, XRD, and HRTEM measurements. The spectroscopic analyses revealed the multiple interaction pathways between rGO and AmB. rGO-AmB exhibited long-term dispersion stability and improved the thermal conductivity of water by 68%. The thermal conductivity increased with increasing concentration of rGO-AmB and temperature. rGO-AmB as an additive to water (0.2%) enhanced the tribological properties of a steel tribopair under the boundary lubrication regime by the significant reduction in friction (70%) and wear (68%). The tribo-induced gradual deposition of an rGO-AmB-based thin film facilitated the interfacial sliding between the steel tribopair and protected it from the wear. The ultralow thickness, excellent dispersibility in water, high thermal conductivity, intrinsic low frictional properties, and good affinity toward the tribo-interfaces make rGO-AmB a potential candidate for aqueous lubricants. © 2020 American Chemical Society.